NUMERICAL STUDY OF TRANSPORT IN A DISSIPATIVE MEDIUM - Barone, PMVB; Smith, C. M.; Galvao, D. S. (American Physical Soc, 1992)
A numerical study of propagation of a particle through a one-dimensional dissipative medium is presented. The medium is composed of several dissipative sections, which are characterized by their friction coefficients eta. In particular, we have considered two types of friction coefficients distributed orderly or disorderly along the chain. For the same relative proportion of the coefficients, we have found that transport can be enhanced in the disordered distribution in comparison with the ordered one. We also show how this can be considered an approximated way to treat the propagation in a dissipative medium with a position-dependent friction coefficient.